Inferior Alveolar Nerve Damage after Mandibular Third Molar Surgical Extraction in Dental Patients Visiting 28 Military Dental Centre, Lahore - Iqbal, Kanza; Khan, Sarfaraz; Umar, Maryam; Muhammad Afzal; Khan, Shafi Ullah; Mahmood, Khalid (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the frequency of inferior alveolar nerve injury after mandibular third molar extraction. Study design: Descriptive case series. Place and Duration of the study: 28 Military Dental Centre, Lahore from December-2024 to May-2025. Methodology: A total of 250 patients were included who required extraction of impacted mandibular third molar tooth located nearby the inferior alveolar nerve with a Pederson scale difficulty index > 4. Patients were assessed on day two, day seven and at three months for damage to the inferior alveolar nerve. Frequency of the nerve damage was stratified by age & gender and post-stratification comparison was performed using Chi-square test. Results: In this study, 250 patients were included. Median age was 31.00 (9.00) years with 118 (47.20%) patients having age 20-30 years and 132 (52.80%) were aged 31-40 years. There were 116 (46.40%) male and 134 (53.60%) female patients. Among patients who underwent surgical extraction of the mandibular third molar, frequency of IAN damage was 12 (4.80%). Conclusion: Frequency of damage to inferior alveolar nerve after extraction of impacted mandibular third molar tooth was 4.80%.